2014
DOI: 10.3402/ijch.v73.25070
|View full text |Cite
|
Sign up to set email alerts
|

Inuit parent perspectives on sexual health communication with adolescent children in Nunavut: “It's kinda hard for me to try to find the words”

Abstract: BackgroundFor Inuit, the family unit has always played a central role in life and in survival. Social changes in Inuit communities have resulted in significant transformations to economic, political and cultural aspects of Inuit society. Where the family unit was once the setting for dialogue on family relations and sexuality, this has largely been replaced by teachings from the medical community and/or the school system.ObjectiveThe purpose of this study was to explore Inuit parent perspectives on sharing kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 39 publications
(39 reference statements)
5
26
0
Order By: Relevance
“…They almost universally rejected the school system, the nurse/community health representative and the Internet as preferred sources of knowledge about sexual health and relationships. The protective benefits of parent–adolescent communication about sexual health are well known (8,10,27,52). In a youth sexual health study in Greenland, Rink, Montgomery-Anderson and Anastario found that the influence of having a parent/guardian to speak with about topics related to sex, including the consequences of pregnancy, was a key protective factor in reducing STIs among Greenlandic youth (44).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They almost universally rejected the school system, the nurse/community health representative and the Internet as preferred sources of knowledge about sexual health and relationships. The protective benefits of parent–adolescent communication about sexual health are well known (8,10,27,52). In a youth sexual health study in Greenland, Rink, Montgomery-Anderson and Anastario found that the influence of having a parent/guardian to speak with about topics related to sex, including the consequences of pregnancy, was a key protective factor in reducing STIs among Greenlandic youth (44).…”
Section: Discussionmentioning
confidence: 99%
“…Westernization and colonization have been identified in the literature as negative influences on sexual health because of the loss of the accumulated wisdom and knowledge of Inuit regarding the life cycle, reproductive health and family planning which are no longer shared by Inuit families, and contributed to many Inuit parents and grandparents no longer feeling competent to instruct their children (1,18,26,27). …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…From 2003 to 2009, the rate of teenage pregnancy has grown from 118.8 to 161.3/1,000 in Nunavut, roughly four times higher than for other Canadian teens in the same year (7,9). In comparison to the Canadian population as a whole in 2009, 20% of births in Nunavut occurred among women aged between 15 and 19 years, in contrast with only 4% for Canadian women within the same age group (6).…”
Section: Frequencymentioning
confidence: 99%
“…The youngest generation of adults has suffered from this cultural break and had to learn about sexuality almost solely from medical resources, school system and internet (9,20,47). Inuit parents from Nunavut admitted having trouble explaining the concepts of a healthy sexual life to their teenaged children partly due to the traumatic experiences of residential schools (9). In 2004, the majority of Inuit students felt that they were not taught enough in school about sexually transmitted infections and contraception (20).…”
Section: Cultural Insightsmentioning
confidence: 99%